2014
DOI: 10.1177/0022429414554230
|View full text |Cite
|
Sign up to set email alerts
|

“Are You Only an Applauder?” American Music Correspondence Schools in the Early Twentieth Century

Abstract: The purpose of this study was to examine correspondence schools of music in the early twentieth century. Advertisements in widely circulated household and music periodicals and archival copies of courses from Siegel-Myers Correspondence School of Music, United States School of Music, American College of Music, and others were examined. Research questions focused on course offerings, faculty, recruitment, and reputation of the schools. The study also examined the advantages and disadvantages of this first gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…This suggests that each individual popular musician avails of the various technologies available to them to further their informal musical learning. This is not a new phenomenon, as demonstrated by Vogel's (2015) study of music correspondence schools in the early twentieth century, which utilized the relatively new technology of the postal service, and Linklater's (1997) investigation of audio and video music education resources for young instrument learners. Ready and relatively inexpensive access to recorded music influenced the learning strategies of Green's research participants who learned by listening and copying (along with a number of the adult Rock Jam staff), while many younger learners appear to be making use of widespread access to high-speed internet and the many affordances of YouTube.…”
Section: Is Youtube Changing How Popular Musicians Learn?mentioning
confidence: 99%
“…This suggests that each individual popular musician avails of the various technologies available to them to further their informal musical learning. This is not a new phenomenon, as demonstrated by Vogel's (2015) study of music correspondence schools in the early twentieth century, which utilized the relatively new technology of the postal service, and Linklater's (1997) investigation of audio and video music education resources for young instrument learners. Ready and relatively inexpensive access to recorded music influenced the learning strategies of Green's research participants who learned by listening and copying (along with a number of the adult Rock Jam staff), while many younger learners appear to be making use of widespread access to high-speed internet and the many affordances of YouTube.…”
Section: Is Youtube Changing How Popular Musicians Learn?mentioning
confidence: 99%
“…20th centuries, Vogel (2015) found that many correspondence schools offered lessons in instrumental music in addition to music theory, history, and teacher education courses. With the birth of recording technology, it became possible to expand the scope of distance music education.…”
mentioning
confidence: 99%
“…Distance education, “a method of teaching where the student and teacher are physically separated” has evolved alongside technological advancements from audio recordings, radio, television, computers, and the internet (Kentnor, 2015, p. 22). In a review of music correspondence courses that became popular in the late 19th and early 20th centuries, Vogel (2015) found that many correspondence schools offered lessons in instrumental music in addition to music theory, history, and teacher education courses. With the birth of recording technology, it became possible to expand the scope of distance music education.…”
mentioning
confidence: 99%